Smart Home Berbasis IoT Menggunakan Suara Pada Google Assistant - Ajib Hanani; Mokhamad Amin Hariyadi (Jurnal Ilmiah Teknologi Informasi Asia, 2020)
This research builds an IoT based Smart Home using voice command on Google Assistant. It is a solution for sick people who are in wheelchairs / beds or people with disabilities but can speak or elderly people who cannot reach the switch in order to turn on / turn off home devices. In addition, we able to control home devices from any where. The system is built using voice command on the Google Assistant application. Google Assistant converts the voice command to the text command. And then, the text command is forwarded from Google Assistant to Webhooks by IFTTT. Webhooks makes a request to the HTTP RESTful API. The text command is published to MQTT Broker by phpMQTT library available on the HTTP RESTful API. ESP32 Dev Kit as an internet connected microcontroller receives text command from MQTT Broker to turn on or turn off the lights in home. The system testing has succeeded in turning on and turning off the lights with voice commands using Google Assistant.